Formulation and Evaluation of Candlenut (Aleurites moluccana L.) Oil in Gel Preparation - L, Leny; Ginting, Evi Ekayanti; Hafiz, Ihsanul (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The purpose of this study was toformulate a gel preparation from the candlenut (Aleurites moluccana) oil. Theresulting formula was evaluated bytest of organoleptic, homogeneity, surface dispersion, pH value, and gel stability during storage. Design:This research was conducted by making a gel preparation containing candlenut oil as the active ingredient with various concentrations. The basic ingredients used were carbopol, hydrogenated castor oil (HCO), propylene glycol, methyl paraben, propyl paraben and distilled water. Evaluation of formula and stability was carried out in storage for 12 weeks. Formula tests were carried out to assess the physical form of the preparation, the resulting pH, and the stability during storage. Interventions:The formulas were varied in three different concentrations of active substances, namely 15%, 20% and 25% candlenut oil. Evaluation of formulawas compared with negative control, gel base without active substances. Main outcome measurement:The results show that the resulting gel has a consistency similar to general gel (semisolid), white in color and has the smell of candle oil. The whole gel has good homogeneity. The pH value of each formula is around 6.0-6.4. The surface dispersibility diameter is 5.3-5.7 cm. The whole formula is stable in storage for 12 weeks. Conclusion:Candlenut oil can be formulated in gel form and has good characteristics and stability. Keywords: Aleurites moluccana, formula evaluation, gel formulation